2009
DOI: 10.4314/eamj.v77i7.46684
|View full text |Cite
|
Sign up to set email alerts
|

Ventriculoperitoneal shunt surgery and shunt infections in children with non-tumour hydrocephalus at the Kenyatta National Hospital, Nairobi

Abstract: Objective: To study infections complicating ventriculoperitoneal (VP) shunt surgery in children with non-tumour hydrocephalus at the Kenyatta National Hospital, Nairobi. Design: A retrospective survey. Setting: Kenyatta National Hospital, Nairobi between January 1982 and December 1991. Subjects: Three hundred and forty five patients who underwent V-P shunt placement for non-tumour hydrocephalus. Results: Three hundred and forty five patients underwent V-P shunt placement for nontumour hydrocephalus. There were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
16
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 14 publications
6
16
2
Order By: Relevance
“…The infectious complication rate was 9.1%, which is comparable to the 9.7% rate reported in the standard-setting recent large-scale Ugandan study, and encouragingly lower than the 20%-50% range generally reported in most studies from Sub-Saharan Africa and other developing countries over the past decade. 12, 15,16,18,20,21,25 In fact, our rate of infectious complications lies just outside the 2%-9% range of infectious complications currently reported in North America. 6 The overall rate of pure mechanical failure (that is, not complicated by infection) was 11%.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The infectious complication rate was 9.1%, which is comparable to the 9.7% rate reported in the standard-setting recent large-scale Ugandan study, and encouragingly lower than the 20%-50% range generally reported in most studies from Sub-Saharan Africa and other developing countries over the past decade. 12, 15,16,18,20,21,25 In fact, our rate of infectious complications lies just outside the 2%-9% range of infectious complications currently reported in North America. 6 The overall rate of pure mechanical failure (that is, not complicated by infection) was 11%.…”
Section: Discussionmentioning
confidence: 75%
“…By comparison, yearly volumes in the regional literature ranged from 34 to 50. 15,18,20 Predictors of Outcome Sex. Fifty-three percent of the patients were male in our study, which is consistent with a previously reported male preponderance in hydrocephalus.…”
Section: Patient Volumesmentioning
confidence: 99%
“…Staphylococcus aureus was reportedly a common organism in studies from Kenya and Nigeria. 4,5 But in Uganda, where neonatal ventriculitis is the most common cause of infant hydrocephalus, 11 we recently found evidence for a high prevalence of enteric organisms, especially Acinetobacter species, in the CSF of these infants, as well as in their home environments. 3 While clindamycin and rifampicin are effective against staphylococcal species, this is not true for gram-negative and enteric organisms.…”
mentioning
confidence: 97%
“…In a retrospective review of 345 cases involving children with VP shunts at Kenyatta National Hospital, Nairobi, Mwang'ombe et al found an infection rate of 25%. 6 In Dar es Salaam, Kinasha et al reported an infection rate of 25%, an obstruction rate of 32%, and a combined complication rate of 46% in 65 children, 18% of whom were less than 6 months old. 2 Avoidance of a CSF shunt is particularly desirable in infants with extreme macrocephaly.…”
Section: Discussionmentioning
confidence: 99%